Effect of salinity acclimatisation and administration of hormones on oocyte maturation, ovulation and spawning of goldspot mullet Liza parsia (Hamilton, 1822) reared in brackishwater pond - Kumar, Prem; Biswas, G.; Ghoshal, T.K.; Christina, L.; Behera, P.; Kailasam, M. (Indian Journal of Fisheries, 2020)
Two separate experiments were conducted to evaluate the effect of salinity acclimatisation and administration of hormones on oocyte growth of Liza parsia (Hamilton, 1822). In the first experiment, broodstock fishes in the sex ratio of 2:1 (male:female) were acclimatised to 30 ppt salinity (which is the desired salinity for breeding L. parsia) in 24, 48 and 72 h of duration (n=6). Oocyte diameter from the experimental fishes were measured before and after salinity acclimatisation. The results showed that the acclimatisation to breeding salinity reduced oocyte diameter (p<0.05) in female fish and increased sperm relative mortality (p<0.05) in male fish. In the second experiment, males and females in the similar sex ratio (2:1) were acclimatised to the desired salinity of 30 ppt in 24 h. Subsequently, carp pituitary gland extract (PGE), human chorionic gonadotropin (HCG), combination of PGE+HCG and luteinising hormone releasing hormone analogue (LHRHa) with dopamine antagonist (DA) metoclopramide were injected intramuscularly, The dosages used were: PGE- 0.01 and 0.02 mg g-1; HCG - 20 and 40 IU g-1, LHRHa - 10 and 20 µg kg-1 as primary and secondary doses, respectively. Metoclopramide was injected at the dose of 15 mg kg-1 along with LHRHa. Results of the second experiment indicated that the administration of PGE or PGE+HCG is essential for final oocyte maturation and ovulation in salinity acclimatised L. parsia.Keywords: Dopamine antagonist, Gonadotropin, Liza parsia, Luteinizing hormone, Oocytes growth, Salinity